2022
DOI: 10.1001/jamacardio.2021.6016
|View full text |Cite
|
Sign up to set email alerts
|

Association of Premature Ventricular Contraction Burden on Serial Holter Monitoring With Arrhythmic Risk in Patients With Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: IMPORTANCEA high burden of premature ventricular contractions (PVCs) at disease diagnosis has been associated with an overall higher risk of ventricular arrhythmias in arrhythmogenic right ventricular cardiomyopathy (ARVC). Data regarding dynamic modification of PVC burden at follow-up with Holter monitoring and its impact on arrhythmic risk in ARVC are scarce.OBJECTIVE To describe changes in the PVC burden and to assess whether serial Holter monitoring is dynamically associated with sustained ventricular arrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…Similar to our findings, one recent observational study examining patients with multiple Holter monitors found that the average burden of PVC decreased after initial diagnosis. 10 This study likewise demonstrated the importance of changes in PVC count, with both presence of NSVT and increase in PVC burden independently identifying increased risk for VA events in the year following assessment. Cappelletto et al 17 likewise found that both NSVT and PVC burden decreased progressively at both 2-year and 8-year follow-up in their cohort of patients with repeat Holter monitoring and that NSVT remained an important independent risk factor for VA at follow-up.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar to our findings, one recent observational study examining patients with multiple Holter monitors found that the average burden of PVC decreased after initial diagnosis. 10 This study likewise demonstrated the importance of changes in PVC count, with both presence of NSVT and increase in PVC burden independently identifying increased risk for VA events in the year following assessment. Cappelletto et al 17 likewise found that both NSVT and PVC burden decreased progressively at both 2-year and 8-year follow-up in their cohort of patients with repeat Holter monitoring and that NSVT remained an important independent risk factor for VA at follow-up.…”
Section: Discussionsupporting
confidence: 61%
“…8 However, ARVC is a progressive condition, and clinical predictors included in the ARVC risk calculator may be dynamic. [9][10][11] How reliably this tool performs at subsequent evaluations after initial diagnosis is, therefore, unknown, limiting longitudinal risk assessment in these patients.…”
mentioning
confidence: 99%
“…In keeping with this, recent data tracking ARVC patients longitudinally over time have also suggested that 5-year VA risk drops by nearly 50% between the time of initial diagnosis and 5-year follow-up. 24 , 25 It is therefore possible that enrolment of European patients later in the disease process may have contributed to their observed lower rate of VA events. Importantly, prior studies have demonstrated adequate calibration of the ARVC risk calculator in both European and North American patients, 9 , 10 and thus, these phenotypic discrepancies are accounted for during calculation of VA risk.…”
Section: Discussionmentioning
confidence: 99%
“…While sotalol had historically been considered the most effective for this indication based on data from the 1992 Wichter et al [ 39 ] study, the Trieste Heart Muscle Disease Registry in Capelletto et al, did not demonstrate any benefit with sotalol, and the North American ARVC Registry studied in Marcus et al, even suggested a negative effect with an increased risk of ICD shock and clinically relevant arrhythmia. In their study, Marcus et al, acknowledge the potential for confounding by indication, where the likelihood of having arrhythmias could affect the administration of sotalol.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients with a high or dynamic increase in PVC burden also warrant consideration. A recent 2022 retrospective cohort study by Gasperetti et al, demonstrated that the presence of NSVT and/or PVC spikes at a follow-up Holter examination were associated with sustained VA in the following 12 months [ 39 ]. A dynamic risk estimation from annual Holter monitor data can prompt the initiation or titration of AAD in an effort to reduce the subsequent risk of major VAs.…”
Section: Current Practice At the Johns Hopkins Hospitalmentioning
confidence: 99%